REPERCUSSIONS OF THE DEMOCRATIZATION OF ARTIFICIAL INTELLIGENCE ON PERSONALITY RIGHTS - Diniz, Maria Helena; Santiago, Mariana Ribeiro; Costa, Déborah Regina Lambach Ferreira da (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2026)
The present article deals with the interface between the current dissemination of artificial intelligence and personality rights. The choice of topic is justified by the uncertainties caused by the use of such technology in various sectors. The aim is to provide a legal framework for the use of AI, guaranteeing respect for the human person and personality rights. In order to do this, the paper discusses AI as a vector for global development in the 21st century, the dangers that AI can represent in the medical-scientific field, the repercussions of AI on educational law and the impact of AI on intellectual property. The approach used was Miguel Reale's dialectical method, combined with bibliographic and documentary research procedures.